Analisis Faktor-Faktor yang Mempengaruhi Adopsi Aplikasi MyTEnS dengan Model Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) Pada Account Manager di Telkom Indonesia - Tricahyono, Dodie Febri; Wiryawan, Yosef; Awaluddin, Muhammad (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
To continue building performance excellence, Telkom launched five main strategies known as the Five Bold Moves strategy (Infraco, Data Center, B2B IT, Digico and FMC). Telkom Indonesia developed the MyTEnS application to create smoother and more efficient B2B business processes for Account Managers. This study seeks what factors influence MyTEnS adoption and which moderating variables will strongly moderate the acceptance of MyTEnS adoption. This research uses quantitative methods and the expanded UTAUT-2 model with the addition of Personal Innovativeness and Age and Job Tenure variables will become Moderation variables. This study used a sample of 129 respondents. Data analysis in this study uses path analysis using the SmartPLS program. The results of testing the hypothesis can be concluded that Effor expectancy, Hedonic motivation, and Personal innovativeness have a positive and significant influence on Behavioral Intention. Facilitating Conditions and Behavioral Intention have a significant positive effect on Use Behavior.